SOSIALISASI PAJAK NATURA BAGI KARYAWAN INDUSTRIAL AND COMMERCIAL BANK OF CHINA - Lukman, Hendro; Wijaya, Purnamawati Heln; Young, Amanda (Jurnal Bakti Masyarakat Indonesia, 2024)
Natura is a reward or enjoyment given by an employer to its employees not in the form of money. Intrinsically, receiving rewards can increase the economic capabilities of the recipient. However, not all in kind provided by the company can be a burden for the company. The regulation of giving in kind has been regulated by tax law since the tax reform was carried out in 1983, but looking at its implementation there is still uncertainty. In line with the increase in state income, Minister of Finance Regulation (PMK) Number 66 of 2023 concerning Natura Tax was issued. This PMK aims to provide certainty in Natura tax arrangements for companies and employees. The new PMK will be issued at the end of June 2023. The Community Service Team for the Undergraduate Accounting Study Program provides outreach to stakeholders, one of which is the Industrial and Commercial Bank of China (ICBC) Central Park branch. This Community Service method is to provide socialization. The purpose of this socialization is so that employees know the Natura rules well, and prepare annual tax return (SPT) for year 2023. The socialization was carried out at partner offices and was attended by 11 participants. This socialization was considered to have gone well and provided participants with a better understanding. This can be seen from the results of the evaluation carried out at the end of the socialization. This activity is a community outreach activity for stakeholders, including foreign companies operating in Indonesia by Tarumanagara University. ABSTRAK Natura merupakan suatu imbalan atau kenikmatan yang diberikan pemberi kerja kepada pekerjanya tidak dalam bentuk uang. Secara intrinsik, penerimaan imbalan dapat meningkatkan kemampuan ekonomis bagi penerimanya. Namun tidak semua natura yang diberikan perusahaan dapat menjadi beban bagi perusahaan. Pengaturan pemberian natura ini sudah diatur oleh undang-undang perpajakan sejak dilakukannya reformasi perpajakan tahun 1983, namun melihat implementasinya masih terdapat ketidakjelasan. Seiring dengan peningkatan pendapatan negara, maka dikeluarkan Peraturan Menteri Keuangan (PMK) Nomor 66 tahun 2023 tentang Pajak Natura. PMK ini bertujuan memberikan kepastian pengaturan perpajakan Natura bagi perusahaan dan karyawan. PMK yang baru dikeluarkan akhir Juni 2023. Tim Pengabdian Kepada Masyarakat Program Studi S1 Akuntansi memberikan sosialisasi kepada pemangku kepentingan, salah satunya kepada Industrial and Commercial Bank of China (ICBC) cabang Central Park. Metode Pengabdian Kepada Masyarakat ini adalah memberikan sosialisasi. Tujuan sosialisasi ini adalah agar karyawan mengetahui aturan Natura dengan baik, dan menyiapkan laporan Surat Pemberitahuan (SPT) Tahunan tahun 2023 dengan benar. Sosialisasi dilakukan di kantor mitra yang diikuti oleh 11 peserta. Sosialisasi ini dinilai berjalan dengan baik dan telah memberikan pemahaman yang lebih baik kepada peserta. Ini terlihat dari hasil evaluasi yang dilakukan di akhir sosialisasi. Kegiatan ini merupakan kegiatan pengabdian kepada masyarakat kepada pemangku kepentingan, termasuk perusahaan asing yang beroperasi di Indonesia oleh Universitas Tarumanagara.